Comparison Of Clinical Studies Learning Microskill Model And Learning Achievement Domains Against The Conventional Clinical Nursing Students Study Program D3 Magelang Polytechnic Ministry Of Health Semarang - Saseno Saseno; Sunarko Sunarko; Moh Hanafi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
The Objective of study is Knowing the Difference between Clinical Learning Microskill Model and Learning Achievement Domains Against the Conventional Clinical Nursing Students Study Program D3 Magelang polytechnic ministry of health Semarang. Research approach was quantitative and quasi-experimental research design. Research subjects consisted of 38 third-year students of Nursing Studies Program Magelang Polytechnic ministry of health Semarang. The experimental group consisted of 19 students and a control group consisted of 19 students, with the sampling method was accidental sampling. The instrument used was a form of nursing care assessment conducted of students, professional attitude assessment format, and format of assessment komptetensi clinical practice. Interventions provided are learning model microskill clinic model, which performed during 2 months in a clinical practice rotation. The difference value of good clinical practice the cognitive domains and affective domains in the experimental group there were significant differences when compared with the control group.